Soil Fertility Level In The Aek Kundur River Area Regardless Of Factory Waste Disposal - Surya Ramadani Pane, Risky; Lestari , Widya; Walida , Hilwa; Hariyati Adam , Dini (Publisher Cv. Inara, 2024)
Soil fertility is the ability of the soil to provide the nutrients needed by plants in adequate quantities and in a form that can be absorbed by plant roots. The aim of this research is to determine the level of soil fertility in the Aek Kundur river area regarding factory waste disposal in Lingga Tiga Village, District. West Bar. This research was carried out in June 2024 in Lingga Tiga Village, Bilah Hulu District, Labuhanbatu Regency with an altitude of 28 meters above sea level with coordinates N: 98022'44.34